Pengaruh Posisi Kas, Current Ratio, Debt to Equity Ratio dan Gross Profit Rratio terhadap Return Saham ( Studi empirik pada Perusahaan Yang Terdaftar Dalam Jakarta Islamic Index Bursa Efek Indonesia 2004-2007) - Nandang Munandar (Eqien - Jurnal Ekonomi dan Bisnis, 2018)
The aim of the research is to trial the influence Cash Position, Current Ratio, Debt to Equity Ratio and Gross Profit Ratio to return stock on companies of the Jakarta Islamic Index in Bursa Efek Indonesia (BEI) This research relating to research of Ball and Brown (1968) increase of the stock price, if the expected return to be larger from the unexpected return, and show it’s the decrease of the stock price, if the expected return to be smaller from the unexpected.The objects of this research are 11 companies of the Jakarta Islamic Index in Indonesian Stock during 2004-2007. The research method used to multiple linier regression, by analyzing the influence of influence Cash Position, Current Ratio, Debt to Equity Ratio and Gross Profit Ratio to return stock is selected both simultaneously or partially. This research uses classic/BLUE assumption test, F test and t test by using SPSS Program version 15. The result of research shows that the simultaneous use of Cash Position, Current Ratio, Debt to Equity Ratio and Gross Profit Ratio not significantly influence the return stock whose result can bee seen in Annova table 0,761. Further, whereas the result of t test shows that the partial use of Cash Position, Current Ratio, Debt to Equity Ratio and Gross Profit Ratio do not significantly influence the return stock whose result 0,133, 0,316, 0,225, dan 0,413. The Conclusion of this research is not consistently with the past research is selected both simultaneously or partial. Key Word : Return Stock, Cash Posisition, Current Ratio, Debt To Equity Ratio and Gross Profit Ratio